2022
DOI: 10.3389/fbioe.2022.789629
|View full text |Cite
|
Sign up to set email alerts
|

Overstretching Expectations May Endanger the Success of the “Millennium Surgery”

Abstract: Total hip arthroplasty (THA) is an extremely successful treatment strategy. Patient expectations, however, have increased; if not properly guided by surgeons, at present, patients expect next to pain-free restoration of the joint and a fast return to work and sports. While the revision rates after THA also increased in younger patients, knowledge on musculoskeletal loads still remains sparse, and the current recommendations on postoperative rehabilitation are based on expert opinions only. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 117 publications
(329 reference statements)
0
5
0
Order By: Relevance
“…Aseptic loosening occurred in three low-activity patients and only one high-activity patient. The risk of aseptic loosening due to implant wear is frequently cited as an argument against high activity [5,6,19,37]. However, the current findings suggest that, despite the biomechanical proof of increased wear due to increased forces, actual clinical findings may not justify general advice against high physical activity [17,18].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Aseptic loosening occurred in three low-activity patients and only one high-activity patient. The risk of aseptic loosening due to implant wear is frequently cited as an argument against high activity [5,6,19,37]. However, the current findings suggest that, despite the biomechanical proof of increased wear due to increased forces, actual clinical findings may not justify general advice against high physical activity [17,18].…”
Section: Discussionmentioning
confidence: 55%
“…They also found that working-age patients showed higher contact loads compared to retirement-age patients during daily activities. Based on these results, it has been suggested that recommendations of sporting activities should be mainly focused on low-impact activities, especially for younger patients [37]. Higher revision rates for younger patients and males compared to females have been reported previously.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Following total joint arthroplasty, the torsional moment around the femoral shaft axis or the tibial axis is a crucial parameter greatly influencing micromotion at the implant-bone interface 19,39 . For patients who underwent THA, the maximal torsional moment around the femoral shaft axis at all velocities in breaststroke swimming (median, 0.87% BWm) in this study was lower than the values reported in weight-controlled walking (1.53% BWm) 9 and common physiotherapies (2.18% BWm) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The contact force direction was determined as the angle α between F Res and the vertical axis in the frontal plane and the angle β between F Res and the vertical axis in the sagittal plane. Additionally, the torsional moment (M Tors ) around the femoral shaft axis or the tibial axis, the bending moment (M Bend ) at the middle of the femoral neck, and the torsional moment (M Tne ) around the femoral neck axis were calculated by previously described methods 19 . The mediolateral force distribution in the knee was calculated as the medial force ratio (MFR) between the medial axial force (F Med ) and the sum of F Med and the lateral axial force (F Lat ) 20,21 (Fig.…”
Section: Methodsmentioning
confidence: 99%